Microtubule‐dependent transport of vimentin filament precursors is regulated by actin and by the concerted action of Rho‐ and p21‐activated kinases. Issue 7 (20th March 2014) - Robert, Amélie; Herrmann, Harald; Davidson, Michael W.; Gelfand, Vladimir I.
ABSTRACT: Intermediate filaments (IFs) form a dense and dynamic network that is functionally associated with microtubules and actin filaments. We used the GFP‐tagged vimentin mutant Y117L to study vimentin‐cytoskeletal interactions and transport of vimentin filament precursors. This mutant preserves vimentin interaction with other components of the cytoskeleton, but its assembly is blocked at the unit‐length filament (ULF) stage. ULFs are easy to track, and they allow a reliable and quantifiable analysis of movement. Our results show that in cultured human vimentin‐negative SW13 cells, 2% of vimentin‐ULFs move along microtubules bidirectionally, while the majority are stationary and tightly associated with actin filaments. Rapid motor‐dependent transport of ULFs along microtubules is enhanced ≥5‐fold by depolymerization of actin cytoskeleton with latrunculin B. The microtubule‐dependent transport of vimentin ULFs is further regulated by Rho‐kinase (ROCK) and p21‐activated kinase (PAK): ROCK inhibits ULF transport, while PAK stimulates it. Both kinases act on microtubule transport independently of their effects on actin cytoskeleton. Our study demonstrates the importance of the actin cytoskeleton to restrict IF transport and reveals a new role for PAK and ROCK in the regulation of IF precursor transport.—Robert, A., Herrmann, H., Davidson, M. W., and Gelfand, V. I. Microtubule‐dependent transport of vimentin filament precursors is regulated by actin and by the concerted action of Rho‐ and p21‐activated kinases. FASEB J . 28, 2879–2890 (2014). www.fasebj.org